Anthropometrics and knee dynamic valgus as explanatory factors for landing kinetics and ACL injury risk: a female football cohort study - Bikandi, E.; Amú-Ruiz, F.; Gómez, A.; Lekue, J. A.; Larruskain, J.; Monasterio, X.; Arce, J.; Setuain, I.; Izquierdo, M. (British Journal of Sports Medicine, 2021)
Background Due to the devastating impact of the anterior cruciate ligament (ACL) injury has on the female athlete´s career, anthropometrics and biomechanics-related risk factor screenings have been widely designed. However, the relation of aberrant movement patterns and other anthropometrical variables still remains controversial. Objective The aim of this study was to analyse if lower limb anthropometrics and knee kinematics could explain landing kinetics during a drop jump maneuver, as primary ACL injury risk factors in a female football environment. Design Prospective cross-sectional descriptive study. Testing methodology was settled inside an anatomical, biomechanical and functional conditioning risk factor screening. Data collection was made during the pre-season period. Setting 4 different teams from the region of the Basque Country (Spain). 2 youth second teams and 2 senior teams competing in the Spanish second division. Patients (or Participants) 64 youth female football players (age 20,32±4,9). Every available (non-injured) athlete was included. No lost participants during the data collection. Interventions (or Assessment of Risk Factors) Pelvic width and femur length were measured as anthropometrical gold variables. Knee valgus kinematics and landing kinetics during the bilateral and unilateral drop jump were registered. Main Outcome Measurements Knee valgus kinematic data (femur-tibia angle <180°) was captured by a video analysis tracker software. Landing kinetics were registered using inertial sensor unit technology Results There was a little correlation (r=0,303) between landing peak VGRF and knee valgus kinematics, at p = 0,01 significance level, and also with the femur length (r=-0,338). In addition, the linear regression analysis showed that the pelvic width, femur length and knee valgus kinematics explained in 89,1% (R2 ) the landing kinetics results (p=<0,005). Conclusions A moderate significance level between lower limb anthropometrics, knee valgus kinematics and landing kinetics was the main finding at the present study. More exhaustive surveillance screening re-tests are needed in order to detect the main contributors for ACL injury mechanics in a female football context.